Tree health and regeneration response of Black Box (Eucalyptus largiflorens) to recent flooding. (20th December 2017) - Moxham, Claire; Duncan, Mike; Moloney, Paul
Summary: Black Box ( Eucalyptus largiflorens ) is a dominant floodplain tree in the Murray–Darling Basin. In northern Victoria, the health of Black Box woodlands has declined as a consequence of river regulation and drought. This has raised concern about the long‐term survival of populations. Although tree health and regeneration of this species are entwined with flooding, there is limited knowledge of its response to environmental watering. This inhibits the effective implementation of management actions to secure the long‐term survival of floodplain Black Box populations. We investigated the effect of flooding history on Black Box tree health, population status and regeneration at 26 sites within the Murray Sunset National Park, Victoria. Sites were assessed under two flooding treatments: (1) 'recently flooded' (sites frequently flooded within the last 5 years and (2) 'historically flooded' (sites not flooded since 1993). Black Box populations in recently flooded sites had a greater range of life stages present and fewer dead trees, indicating a healthier and more sustainable population structure. In addition, trees were in better health with higher canopy condition and reproductive output (e.g. flowers and fruits), and the average tree diameter was greater than in historically flooded sites. Seedlings and saplings were present only at recently flooded sites, indicating that water availability and tree health are a strong determinant of regeneration in these landscapes. Flooding is an important factor in the sustainability of Black Box populations in this Victorian semi‐arid floodplain. A key recommendation is that managed flows should be implemented to target populations in poor condition. Although regular flooding is required to maintain or improve the health of Black Box populations, developing the optimum flow regime (timing, frequency and duration) to facilitate this outcome requires further investigation.